Therapeutic Strategies Against COVID-19 and Structural Characterization of SARS-CoV-2: A Review - Jeong, Gi Uk; Song, Hanra; Yoon, Gun Young; Kim, Doyoun; Kwon, Young-Chan (Frontiers in Microbiology, 2020)
The novel coronavirus, SARS-CoV-2, or 2019-nCoV, which originated in Wuhan, Hubei province, China in December 2019, is a grave threat to public health worldwide. A total of 3,672,238 confirmed cases of coronavirus disease 2019 (COVID-19) and 254,045 deaths were reported globally up to May 7, 2020. However, approved antiviral agents for the treatment of patients with COVID-19 remain unavailable. Drug repurposing of approved antivirals against other viruses such as HIV or Ebola virus is one of the most practical strategies to develop effective antiviral agents against SARS-CoV-2. A combination of repurposed drugs can improve the efficacy of treatment, and structure-based drug design can be employed to specifically target SARS-CoV-2. This review discusses therapeutic strategies using promising antiviral agents against SARS-CoV-2. In addition, structural characterization of potentially therapeutic viral or host cellular targets associated with COVID-19 have been discussed to refine structure-based drug design strategies.